Cell membrane-derived nanovesicles as extracellular vesicle-mimetics in wound healing - Wenwen Li; Huihui Zhang; Lianglong Chen; Chaoyang Huang; Ziwei Jiang; Hai Zhou; Xinxi Zhu; Xiaoyang Liu; Zesen Zheng; Qiuyi Yu; Yufang He; Yanbin Gao; et al. (Materials Today Bio)
Cell membrane-derived nanovesicles (NVs) have emerged as promising alternatives to extracellular vesicles (EVs) for wound healing applications, addressing the limitations of traditional EVs, which include insufficient targeting capability, low production yield, and limited drug-loading capacity. Through mechanical cell extrusion methods, NVs exhibit superior characteristics, demonstrating enhanced yield, stability, and purity compared to natural EVs. These NVs can be derived from various membrane sources, including single cell types (stem cells, blood cells, immune cells, and bacterial membranes), hybrid cell membranes and cell membranes mixed with liposomes, with each offering unique therapeutic properties. The integration of genetic engineering and surface modifications has further enhanced NV functionality, enabling precise targeting and improved drug delivery capabilities. Recent advances in NV-based therapies have demonstrated their potential across multiple biomedical applications. Although challenges persist in terms of standardization, storage stability, and clinical translation, the combination of natural cell-derived functions with artificial modification potential positions NVs as a promising platform for next-generation therapeutic delivery systems, thereby offering new possibilities in wound healing applications. Finally, we explore the challenges and future prospects of translating NV-based therapeutics into clinical practice, providing insights into the future development of this innovative approach in wound healing and tissue repair.